Jual Beli Murabahah dan Salam: Sebuah Tinjauan Literatur Review - Haanii Haritsa Yuzen; Fanisa Suseno; Pujy Yonesha; Aidil Alfin (Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2025)
The purpose of this study is Buying and Selling Murabahah and Greetings: A Review of the Literature Review. This research method is a type of literature research; This means that the information materials used come from library sources in the form of books, encyclopedias, magazines, journals, newspapers, journals, This form of research is descriptive, analytical, and critical. Therefore, the author can comprehensively describe. In this study, the author optimally used two data sources related to this research, namely. Primary data sources and secondary data sources. The main source of this research is books and scientific journals on the Knowledge of the Role of Waqf. At the same time, this research is supported (secondary) by the work of other thinkers . The results of the study This agreement is very relevant for the agricultural sector because it provides initial funds for farmers to produce agricultural products. In addition to providing financing solutions, the Salam contract is also a sharia alternative to avoid exploitative ijon practices. These two contracts have a strong legal basis from the Qur'an, Hadith, as well as fatwas of DSN-MUI and PSAK, and have been proven to make a real contribution to the economic development of the ummah, especially through the Islamic financial system.